(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
What history should be taught is a question that has vexed curriculum designers from the earliest days of mass education. The question of content becomes particularly pertinent when applied to Key Stage 3 (ages 11-14) as learners are old enough to begin appreciating historical concepts and it is usually the last age at which many learners will be exposed to history in their formal schooling. Decisions about the content of history curricula themselves have a curiously circular history. Although these questions have been discussed consistently throughout the approximately one hundred years that mass schooling has been in place in England, the inferences are fairly uniform. The conclusion that has now generally been reached is that children should be exposed to a healthy balance of world and British history; that they should be patriots, but not narrow-minded in their patriotism and that the procedural nature of history must be taught alongside the substantive content. These conclusions have not been reached without considerable debate and the question of what history should be taught has particular current relevance in light of the controversy around the national curriculum reforms in Britain in 2013 and 2014. There are important lessons to be drawn for South Africa.